Towards understanding enabling environments for good practices in disaster risk management: an analysis of critical junctures in Manizales, Colombia. (October 2021) - Wesely, Julia
The city of Manizales in Colombia has been widely recognized as a good practice case in disaster risk management (DRM). Previous research has sought to amplify learning from Manizales through examining the characteristics of its innovative practices. These are championed by an inter-institutional alliance that includes academia, the local government, the regional environmental authority and service providers. This paper argues that this learning needs to be accompanied by a nuanced understanding of the historical trajectories that have allowed Manizales to create and consolidate its current enabling environment for DRM. The argument derives from an analysis of fieldwork data, including semi-structured interviews, participant observation and secondary data, through a critical juncture approach. Focusing on the critical juncture of seasonal heavy rains in 2003, the paper illustrates how institutional changes configured cultural–cognitive, regulatory and normative conditions for the emergence of one of Manizales' most recognized good practices, the Guardians of the Slope programme.